2020
DOI: 10.1159/000507692
|View full text |Cite
|
Sign up to set email alerts
|

How to Intervene in the Caries Process in Children: A Joint ORCA and EFCD Expert Delphi Consensus Statement

Abstract: This paper provides recommendations for dentists for the treatment of dental caries in children, with an emphasis on early childhood caries (ECC), primary teeth, and occlusal surfaces in permanent teeth. A consensus workshop followed by an e-Delphi consensus process was conducted with an expert panel nominated by the European Organization for Caries Research (ORCA) and European Federation of Conservative Dentistry (EFCD)/German Association of Conservative Dentistry (DGZ) boards. Based on 3 systematic reviews a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 25 publications
(25 reference statements)
3
55
0
7
Order By: Relevance
“…Although there was no significant impact of performing a pulpotomy, it is interesting to note that the teeth that were restored without pulp therapy actually showed a longer projected survival time. This seems to lend credence to recent work on the placement of SSCs chair-side that has shown that if there is appropriate case selection, the survival of teeth with proximal caries is not affected by the performance of a pulpotomy [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Although there was no significant impact of performing a pulpotomy, it is interesting to note that the teeth that were restored without pulp therapy actually showed a longer projected survival time. This seems to lend credence to recent work on the placement of SSCs chair-side that has shown that if there is appropriate case selection, the survival of teeth with proximal caries is not affected by the performance of a pulpotomy [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 55%
“…This meant that the SSC, especially when performed under GA, has been combined with a pulpotomy or pulpectomy [ 8 , 12 ]. However, with advent of the Hall technique, there has been an increased recognition of the SSC as a form of minimal intervention dentistry [ 11 ]. This study aimed to evaluate if placing a pulpotomy on teeth with no history of spontaneous pain and proximal dental caries improved the survival outcomes for SSCs placed under GA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The European Federation of Conservative Dentistry (EFCD) and the European Organisation for Caries Research (ORCA) have collaborated in an attempt to collate and generate pragmatic, evidence-based guidance for primary care practitioners. 19,20,21,22,23 These, along with many other published efforts, are trying to help the relevant stakeholders to manage patients, improve oral health linked to general health and increase awareness in populations of their role in valuing and taking responsibility for their personal healthcare future. 24,25 Education and training courses exist to help dentists, dental therapists and team members learn about and implement MIOC (for example, the online, distance-learning master's programme in Advanced Minimum Intervention Dentistry).…”
Section: Minimally Invasive Treatmentsmentioning
confidence: 99%